Non-ionic iodinated contrast-induced sialadenitis with parotid gland sparing in patient of hepatocellular carcinoma. (23rd January 2018) - Azeemuddin, Muhammad; Chaudhry, Mustafa Belal Hafeez; Shahid, Jehanzeb; Belal, Sarosh Zafar
Abstract : 61-years-old male patient presented with complain of neck swelling and soreness following contrast-enhanced (CE) CT examination with resolution of symptoms in 36–48 hours. He is diagnosed with hepatitis C virus and hepatocellular carcinoma (HCC); already treated with radiofrequency ablation for HCC. He had already undergone two CECT examinations before he was referred to our institution for disease staging/treatment. He also underwent three triphasic CT scan examinations at our institution during the course of treatment for treatment response and staging. Patient remained undiagnosed up to his fourth CT scan due to inability to relate symptoms with contrast administration. The patient was offered close monitoring on fifth CT exam and ultrasound of neck revealed enlarged and echogenic bilateral submandibular glands, however, thyroid and bilateral parotid glands appear unremarkable. This represents transient iodinated contrast induced sialadenitis with sparing of parotid glands.